Leksikon Kemaritiman dalam Bahasa Tobelo: Kajian Etnolinguistik Masyarakat Pesisir Pulau Obi - Boriri, Agus (Titian: Jurnal Ilmu Humaniora, 2026)
This research was conducted with the aim of describing the form of lexicon and interpreting the cultural connections contained behind these terms ethnolinguistically. The research relies on qualitative descriptive based on the phenomenological paradigm using an ethnolinguistic approach. The data sources for this research consist of; (1) Local fishermen, (2) Traditional leaders, and (3) Boat builders. In collecting data, this research used the listening method, the conversation method, and continued with recording and note-taking techniques. The data analysis process was carried out through; 1) Obtaining a general overview. 2) Taxonomic analysis. 3) Searching for specific characteristics. 4) Integrating all findings from domain, taxonomic, and componential analysis. The results of the study prove that the Tobelo tribe on Obi Island has a rich marine vocabulary (lexicon) that is very detailed, ranging from fish classification to traditional navigation. The uniqueness of this language is not just a means of communication, but a reflection of their dependence on and ecological adaptation to local waters. Ethnolinguistically, the marine is closely related to cultural identity which is seen as a sacred space containing taboo values. Abstrak Penelitian ini dilakukan dengan tujuan untuk mendeskripsikan bentuk leksikon dan memaknai kaitan budaya yang terkandung di balik istilah-istilah tersebut secara etnolinguistik. Penelitian mengandalkan deskriptif kualitatif yang berpijak pada paradigma fenomenologi dengan menggunakan pendekatan etnolinguistik. Sumber data penelitian ini terdiri dari; (1) Nelayan lokal, (2) Tokoh adat, dan (3) Pembuat perahu. Dalam mengumpulkan data, penelitian ini menggunakan metode simak, metode cakap, dan dilanjutkan dengan teknik rekam dan catat. Proses analisis data dilakukan melalui; 1) Memperoleh gambaran umum. 2) Analisis taksonomi. 3) Mencari ciri spesifik. 4) mengintegrasikan seluruh temuan dari analisis domain, taksonomi, dan komponensial. Hasil penelitian membuktikan bahwa masyarakat suku Tobelo di Pulau Obi memiliki kekayaan kosakata (leksikon) laut yang sangat mendetail, mulai dari klasifikasi ikan hingga navigasi tradisional. Kekhasan bahasa ini bukan sekadar alat komunikasi, melainkan cermin dari ketergantungan hidup dan adaptasi ekologis mereka terhadap perairan setempat. Secara etnolinguistik, kelautan berkaitan erat dengan identitas budaya yang dipandang sebagai ruang sakral mengandung nilai tabu.